Primary care visit preparation and communication for patients with poorly controlled diabetes: A qualitative study of patients and physicians. Issue 2 (April 2017) - Grant, Richard William; Altschuler, Andrea; Uratsu, Connie Si; Sanchez, Gabriela; Schmittdiel, Julie Ann; Adams, Alyce Sophia; Heisler, Michele
Highlights: Many patients with diabetes do not prepare for their primary care visits. Patients that do prepare find that doctors are more likely to discuss their concerns. Doctors report that they can be more productive when their patients are prepared. Tools are needed to help patients identify priorities for time-limited visits Abstract: Objective: The purpose of this study was to examine how patients with diabetes and their primary care physicians identify and discuss visit priorities prior to and during visits. Methods: We conducted a qualitative study involving patients with diabetes (4 focus groups, n = 29) and primary care physicians (6 provider practice meeting discussions, n = 67). Results: Four key themes related to prioritization were identified: 1) the value of identifying visit priorities before the visit; 2) challenges to negotiating priorities during the time-limited visit; 3) the importance of "non-medical" priorities; and 4) the need for strategies to help patients prepare for visits. Both patients and physicians felt that identifying a concise list of key priorities in advance of the visit could help establish collaborative visit agendas and treatment plans. Conclusions: Identifying and communicating mutually agreed upon priorities for discussion is a key challenge for time-limited primary care visits. Practice implications: Communication between primary care physicians and their patients with diabetes could be improved by strategies that help patients identify their top visit priorities before the visit.